Penerapan Model Pembelajaran Sentra dan Implikasinya pada Pengembangan Kecerdasan Majemuk Anak Usia Dini - Amurisi Ndraha; Nesti Tuwenty Waruwu (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Education is important for an individual. Education for early childhood is determined through the application of learning models, one of which is the central learning model. This model is a model that focuses on playing centers during learning. Another term center method from BCCT (Beyond Centers and Circle Time). This model helps children develop their multiple intelligences. The research aims to find out how the application of the learning center model in Elohim Terpadu Christian Private Kindergarten is, to describe the impact of the center learning model to increasing children's multiple intelligences, to explain the strategy for implementing the learning center in order to increase children's multiple intelligences. The research uses qualitative research methods with analytical descriptive nature, which examines the participant's perspective and interactive and flexible strategies. The collected data were analyzed using interactive model technique. The strategy used so that the application of this model can improve children's multiple intelligences, namely preparing playing opportunities, playing alternatives for children every day, providing center teachers who have expertise in the center field.Keywords: learning center model, multiple intelligences, early childhoodAbstrakPendidikan merupakan hal penting bagi suatu individu. Pendidikan bagi anak usia dini ditentukan melalui penerapan model pembelajarannya, salah satunya ialah model pembelajaran sentra. Model ini adalah model yang menitikberatkan sentra bermain saat pembelajaran. Metode sentra istilah lain dari BCCT (Beyond Centers and Circle Time). Model ini, membantu anak mengembangkan kecerdasan majemuk yang ia miliki. Penelitian bertujuan Mengetahui bagaimana penerapan model pembelajaran sentra di TK Swasta Kristen Elohim Terpadu, menggambarkan sejauh mana dampak model pembelajaran sentra bagi peningkatan kecerdasan majemuk anak, menjelaskan strategi penerapan pembelajaran sentra agar mampu meningkatkan kecerdasan majemuk anak. Penelitian menggunakan metode penelitian kualitatif yang sifat deskriptif analitis, yang mengkaji prespektif partisipan dan strategi-strategi bersifat interaktif dan fleksibel. Data yang terkumpul dianalisis menggunakan teknik interactive model. Strategi yang digunakan agar penerapan model ini dapat meningkatkan kecerdasan majemuk anak, yaitu menyiapkan kesempatan bermain, alternatif bermain pada anak setiap harinya, menyediakan guru sentra yang memiliki keahlian dalam bidang sentra.Kata Kunci: model pembelajaran sentra, kecerdasan majemuk, anak usia dini